Sleep monitoring system using pulse sensor / Nurul Sakinah Mohd Ghazaly - Mohd Ghazaly, Nurul Sakinah (2024)
Sleep is a crucial part of life for maintaining optimal brain and body function. However, the rising concern of death while sleeping has called for improving monitoring systems. With the development of the Internet of Things (IoT), sleep monitoring systems can be improved. Hence, with a better sleep monitoring system, the patient’s condition and heart rate can easily be monitored by their carer and health personnel. This study proposed an IoT-based sleep monitoring system utilizing a wearable device with a heartbeat sensor. This project’s hardware development includes heartbeat sensor, reset button for emergency calls, buzzer, LED, and Arduino UNO as the main controller. When an abnormal heartbeat is detected, alerts are triggered through a Wi-Fi module to notify healthcare personnel on their mobile phones. The complete prototype of this system aims to simplify timely action by healthcare providers, ensuring the well-being of patients during sleep.